ANALISIS DUKUNGAN KELUARGA TERHADAP PERILAKU PENGENDALIAN DIABETES PADA PENDERITA DM TIPE II DI PUSKESMAS TANJUNG RAJA : ANALYSIS OF FAMILY SUPPORT FOR DIABETES CONTROL BEHAVIOUR IN TYPE II DIABETES PATIENTS AT PUSKESMAS TANJUNG RAJA - Marlina, Devi; Putri, Ririn Noviyanti (Jurnal Mitra Kesehatan, 2025)
Introduction : The number of people living with diabetes has increased. New cases have increased faster in low- and middle-income countries. The implementation of Diabetes Mellitus disease control is strongly influenced by the support of the family. This study is expected to see an overview of how much family support is obtained by type II diabetes mellitus patients and the relationship between family support and diabetes control behaviour. Method: This study is a correlational study, using a cross sectional approach. The sample used in this study amounted to sixty respondents who suffered from type II diabetes mellitus. The research was conducted at Puskesmas Tanjung Raja, Ogan Ilir on December twenty and twentyfour to twenty and twentyfive. In Diabetes Mellitus control behaviour variables are measured based on four components to be measured, namely drug consumption, physical activity, eating habits, and checking sugar levels in health services. The analysis in this study used univariate analysis and bivariate analysis, and used the Chi Square test on the SPSS application. Result: In the univariate analysis, thirty four patients received family support when performing diabetes control behaviour, and thirtyone patients did not perform diabetes control behaviour. In bivariate analysis there is a significant relationship between family support and diabetes control behaviour. Conclusion: It can be concluded that there is a relationship between family support and diabetes control behaviour in type II diabetes mellitus patients.